Hosszú utazás - Böszörményi, Zsuzsa; Salminen, Kai (Hungary : Böszörményi, Zsuzsa ; Walhforss, Mikael, 2007)
A village in Eastern Europe where for more than a century nationality has changed in a season-like cadenza: first it belonged to the Hapsburg Empire, then to Czechoslovakia, then to the Soviet Union. At the end of World War II, the Russians established a border that divided the village of Szelmenc between two separate countries. Families on one side live in Slovakia, which is now a member of European Union. On the other side, their relatives have to endure the unstable political and economic conditions in Ukraine. While the EU is setting up Schengen borders, people living on the Ukrainian side have become even more isolated with the plans to open a new border crossing. A tragicomic story of geopolitical absurdities and those who suffer from them.
Verzio Film Festival Submission
With voice-over in English
Verzio Film Festival Submission
Keywords: Documentary films